Compressibility of Undisturbed Silt Loam Soil—Measurements and Simulations. Issue 8 (21st August 2015) - Berli, M.; Casini, F.; Attinger, W.; Schulin, R.; Springman, S.M.; Kirby, J.M.
Abstract : The protection of soils against compaction requires knowledge of the mechanical behavior and properties of structured, unsaturated soils at different water suctions. This study of an agricultural silt loam soil is based on undisturbed specimens from the plow layer (7–17 cm depth) and two subsoil layers (47–57 and 67–77 cm depths) conditioned to five initial suctions ( s 0 = 1, 3, 6, 16, 32 kPa) per layer and compressed under drained, confined uniaxial stress. This study shows how effective axial stress vs. void ratio curves can be calculated from experimentally determined total axial stress vs. void ratio curves using a simplified form of Bishop's effective stress equation in conjunction with a modified form of the van Genuchten equation. Casini's unsaturated soil mechanics model was successfully fitted to the effective axial stress vs. void ratio curves. The effective initial precompression stress was simulated reasonably well using initial void ratio, degree of saturation, or suction, respectively, which was determined in this study. The results demonstrate the influence of soil moisture and density on the compression behavior of an undisturbed silt loam soil and show a method for predicting precompression stress as a function of void ratio and soil water status measured as suction or degree of saturation.